Comparative and prospective analysis of three different approaches for live-donor nephrectomy (Clinics, 2009)
PURPOSE: Living donor nephrectomy is usually performed by a retroperitoneal flank incision. Due to the significant morbidity and long recovery time for a flank incision, anterior extra peritoneal sub-costal and transperitoneal video-laparoscopic methods have been described for donor nephrectomy. We prospectively compare the long-term results of donors as well as functional recipients submitted to these three approaches. MATERIALS AND METHODS: A total of 107 live donor renal transplantations were prospectively evaluated from May 2001 to January 2004. Donors were compared with regard to operative and warm ischemia time, postoperative pain, analgesic requirements, and complications. Recipients were compared with regard to graft function, acute cellular rejection, surgical complications, and graft and recipient survival. RESULTS: The mean operative and warm ischemia times were longer in the video-laparoscopic group (p